1970
DOI: 10.1136/thx.25.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function during pregnancy in normal women and in patients with cardiopulmonary disease

Abstract: Pulmonary function studies were carried out during pregnancy in 8 normal women, in 8 patients with valvular (either mitral or aortic) heart disease, and in 8 patients with chronic pulmonary disease (either emphysema or sarcoidosis). In healthy pregnant women, changes in lung volumes and maximal expiratory flow rates were not significant. Diffusing capacity tended to decrease associated with unchanged pulmonary capillary blood volume. In patients with valvular heart disease, ventilation and oxygen consumption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 18 publications
6
31
1
1
Order By: Relevance
“…These results are consistent with the majority of previous studies 2,3,10,11 , although only findings from singleton pregnancies were reported. In contrast, Milne et al 13 found the pulmonary diffusing capacity decreased to a low at 24 weeks of gestation, but their sample included smokers and smoking reduces the pulmonary diffusing capacity.…”
Section: Respiratory Function In Pregnancy 767supporting
confidence: 83%
“…These results are consistent with the majority of previous studies 2,3,10,11 , although only findings from singleton pregnancies were reported. In contrast, Milne et al 13 found the pulmonary diffusing capacity decreased to a low at 24 weeks of gestation, but their sample included smokers and smoking reduces the pulmonary diffusing capacity.…”
Section: Respiratory Function In Pregnancy 767supporting
confidence: 83%
“…Changes in lung capacities during pregnancy may also be attributed to various factors like exercise, increase in body weight, changes in chest wall, position and movement of diaphragm, mobility of thoracic cage, change in intraabdominal and intra-pleural pressures, changes in accessory muscles of respiration and mechanical effect of enlarging breasts. 3,14 The results of Monga et al, 15 Girija P et al, 10 Mokkapatti et al 4 agree with the result of present study of decrease in FVC during pregnancy, whereas the results of Gazioglu et al 16 M J Berry et al, 17 T K Das et al 12 show an FVC to be relatively constant during pregnancy. But the results of Anita Teli et al 18 Grindheim et al 19 and Surekha De et al 9 are at variance from those of present study showing increase in forced vital capacity.…”
Section: Discussionsupporting
confidence: 77%
“…A lax cervix leading to third trimester abortion is treated with a Shirodka suture where ‘bearing down’ may not a good idea in these patients. There are a variety of studies of lung function in human pregnancy, including spirometry,53 lung volumes,53 54 airway resistance,55 maximum mouth pressures,56 gas transfer54 57–59 or maximum oxygen uptake60 during swimming and cycling in the third trimester. Most find normal values and report no complications in women.…”
Section: Pregnancymentioning
confidence: 99%